OFSET PERTAHANAN DALAM KERANGKA PASAL 1320 KITAB UNDANG-UNDANG HUKUM PERDATA : ANALISA IMPLEMENTASI PASAL 43 UNDANG.UNDANG NOMOR 16 TAHUN 2012 TENTANG INDUSTRI PERTAHANAN - , Sylvia ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Based on indonesiaâs defense industries Law No. 16 of 2012, the purpose of defense industries is to ensure armed forces necessities by strengthening domestic defense industries while developing self-defense capabilities. In fact, Indonesian armed forces is still heavily dependent on foreign supplier. Therefore, the defense industries law intends to incrementally shift Indonesian foreign-centric orientation requirement to a strategy that emphasize developing domestic defense industries, by implementing offset policy. According Article 43 of Indonesiaâs Defense Industry Law, the government should prioritize in using domestic arms product rather than foreign product if domestic industries meet the defense requirement, but if the local defense industries has not been able to meet the requirement, the government are allowed to buy from foreign countries. This chapter also regulates on countertrade, local content and/or offset (technology transfer) of at least 85 percent of total contract. Unfortunately, this rigid obligation is burdened not only for foreign industries but also Indonesia Government and defense industries itself. Moreover, this law raises several legal loopholes, first, the law is failed to define what is defense offset, second, form of offset and how it should be conducted related to article 1320 civil code concerning valid agreement requirement. This research aims to define defense offset and its mechanism to support developing domestic defense industries capability. It uses empirical normative legal research and analyze how the shape of Defense Offset according to Law No. 16 of 2012 and its formulation in the context of the applicability of Article 1320 of the Civil Code. This study concluded that there are 4 (four) form of offset that should be implemented such as Direct Defense Offset, Indirect Offset Related to Defense, Indirect Offset of supported, and Indirect Offset of Non-Defense. This form is associated with defense and security equipment procurement cycle. The form and mechanism of offset as an object of offset agreement, while the subject agreement covers Offset Receivers and Providers.